Salin-Salamin: Ang Pagsasa-Filipino ng mga Banyagang Programa - Crisostomo, Leila; de Lara, Ivan Joseph M.; Gallardo, Raia Alexis T.; Singh, Manpreet (Dúnong: UP Diliman Journal of Student Research, 2023)
(no abstract)